The Problem of Finite Verb Translation in Exodus 15.1-18 - Shreckhise, Robert (Journal for the study of the Old Testament, 2008)
This article examines the finite Hebrew verbs in the song in Exod. 15.1-18. This song has long resisted a uniformly accepted translation. Due to its connection with the Exodus narrative and the difficulty of translating finite verbs in Hebrew poetry, some of the translation problems are exacerbated. This study examines the verbs in the song through an aspectual analysis that takes into account the narrative context of Exodus. Three models of translation are considered: the Prophetic Perfect Model, the Sinai Provenance Model, and the Dual Perspective Model. These three models correspond to three views of the verbs in the song: the prophetic perfect, the preterite, and the traditional schema of perfect-past, imperfect-present/modal/future. Though this study does not arrive at any single answer to the verb translation issues, the analysis clearly points out the possibilities and the problems of each model within the song-narrative context.